Changing Clinical Presentations and Survival Pattern in Trisomy 18 - Chien-Chou Hsiao; Lon-Yen Tsao; Hsiao-Neng Chen; Han-Yao Chiu; Weng-Cheng Chang (Elsevier, 2009)
The clinical presentations and survival patterns of infants with trisomy 18 have changed with increasing utilization of prenatal ultrasound and amniocentesis, and improvements in neonatal intensive care. Methods: We obtained data on duration of survival, male to female ratio, and clinical details for patients with trisomy 18, and calculated the prevalence rate. Results: We studied 31 consecutive trisomy 18 infants. The estimated prevalence was 1/4,144. Eleven (35%) were premature infants, and 20 (65%) were full term. Mean birth weight was 1,896 g. Median life expectancy was 12 days; 11 days for males and 14 days for females (p = 0.87). The short-term survival rates of 1 week, 4 weeks, and 6 months were 58%, 32%, and 10%, respectively. The long-term survival rates of 1 year, 2 years, and 3 years were 6%, 6%, and 3%, respectively. Families signed do-not-resuscitate consent forms for five male (50%) and 19 female infants (90%) (p = 0.043). Conclusion: All trisomy 18 infants in this study were preterm or full-term deliveries. Mean birth weight was lower than previously reported, and a high percentage of families signed do-not-resuscitate consent forms. Females did not survive longer than males, due to more females not being resuscitated. Most infants died in the first few weeks of life, but 3-6% of infants lived for ≥ 1 year. The possibility of long-term survival should be considered when counseling parents regarding trisomy 18.